Numeracy musical training for school children with low achievement in mathematics - Rodriguez, Indira Arias [UNESP]; Nascimento, Jessica M. [UNESP]; Voigt, Marcos F.; Santos, Flávia H. (Servicio de Publicaciones de la Universidad de Murcia, 2019)
The present case-control, double-blind, and prospective study investigated the effects of Numeracy Music Training (NMT) on cognitive skills of primary school children. Participating in the study were 42 children aged 8 to 10 years divided into two groups: Low Achievement in Math (N= 21), and Average Achievement in Math (N= 21). The children underwent two assessments before and after NMT. Cognitive tests and behaviour scales were applied regarding variables such as school performance, IQ, working memory, numerical cognition, math’s anxiety and stress. NMT was developed in eight group sessions and aimed to stimulate the systems of numerical cognition and integrate basic musical knowledge, and symbolic representations. After the intervention, through musical training, the children in both groups showed significant improvements in school performance, systems of numerical cognition and working memory, as well as the reduction of mathematics anxiety symptoms.
Entrenamiento musical numérico para niños escolares con bajo rendimiento en matemáticas
Keywords: Dyscalculia Development; Musical training; Numerical cognition; Working memory